Quality Analysis of the Digital Library Website of Universitas Lambung Mangkurat with Webqual 4.0 Method and User Experience Questionnaire (UEQ) - Nurul Huda; Andreyan Rizky Baskara; Nurul Fathanah Mustamin; Yuslena Sari (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
The current digital literature resources are widely provided by various libraries, especially those associated with higher education institutions. One such example of a digital library is the Lambung Mangkurat University Digital Library (Digilib ULM). Pre-evaluation results indicate that around 50% of the issues are related to the quality of the website, such as its appearance and functionality. Therefore, this research examines the quality of the ULM Digital Library to identify indicators that match user preferences and require improvement. The Webqual 4.0 method and User Experience Questionnaire are uti- lised for this purpose. The research is quantitative with a descriptive approach. Data is collected through a questionnaire, with 100 respondents sampled from the entire population, consisting of ULM students. Webqual 4.0 comprises three dimensions: usability, information quality, and service interaction. Meanwhile, UEQ consists of six aspects: attractiveness, dependability, efficiency, perspicuity, stimulation, and novelty. The research findings from Webqual 4.0 indicate a service interaction score of 2.75, information quality of 2.68, and usability of 2.45. The usability aspect falls into the low category or does not meet user expectations, while the other aspects fall into the moderate category. The UEQ results show an attractiveness score of 1.130, efficiency of 0.648, and novelty of 0.673, all scoring below the average compared to benchmarks, while other aspects score above average. Based on these results, it is evident that the Digilib ULM website does not meet user expectations and can be considered suboptimal, requiring improvement and enhancement.